Fingerprinted secret sharing steganography for robustness against image cropping attacks - Potdar, Vidyasagar; Han, Song; Chang, Elizabeth (IEEE, 2005)
Steganography is the art and science of hiding information. In this paper we propose a conceptual framework for Fingerprinted Secret Sharing Steganography. We offer a technique to break the main secret into multiple parts and hide them individually in a cover medium. We use a novel technique to compress the data to a considerable extent. We use the Lagrange Interpolating Polynomial method to recover the shared secret. We also show how the proposed technique can offer robust mechanism to protect data loss because of image cropping. We use the (k,n) threshold scheme to decide the minimum number of parts required to recover the secret data completely. The security of our scheme is based on the security principle of steganography and secret sharing scheme.